Error-related brain activity dissociates hoarding disorder from obsessive-compulsive disorder. Issue 2 (29th September 2015) - Mathews, C. A.; Perez, V. B.; Roach, B. J.; Fekri, S.; Vigil, O.; Kupferman, E.; Mathalon, D. H.
Abstract : Background: Obsessive-compulsive disorder (OCD) is associated with an abnormally large error-related negativity (ERN), an electrophysiological measure of error monitoring in response to performance errors, but it is unclear if hoarding disorder (HD) also shows this abnormality. This study aimed to determine whether the neurophysiological mechanisms underlying error monitoring are similarly compromised in HD and OCD. Method: We used a visual flanker task to assess ERN in response to performance errors in 14 individuals with HD, 27 with OCD, 10 with HD+OCD, and 45 healthy controls (HC). Age-corrected performance and ERN amplitudes were examined using analyses of variance and planned pairwise group comparisons. Results: A main effect of hoarding on ERN ( p = 0.031) was observed, indicating ERN amplitudes were attenuated in HD relative to non-HD subjects. A group × age interaction effect on ERN was also evident. In HD-positive subjects, ERN amplitude deficits were significantly greater in younger individuals ( r = −0.479, p = 0.018), whereas there were no significant ERN changes with increasing age in OCD and HC participants. Conclusions: The reduced ERN in HD relative to OCD and HC provides evidence that HD is neurobiologically distinct from OCD, and suggests that deficient error monitoring may be a core pathophysiological feature of HD. This effect was particularly prominent in younger HD participants, further suggesting that deficient error monitoring manifests most strongly early in the illness course and/or in individuals with a relatively early illness onset.